G461(P) Lung function measurement following surgery in idiopathic scoliosis. (12th March 2018) - Williams, IE; Finnerty, E; Rutter, M; Khan, M; Charlton, S; Ross Russell, R
Abstract : Background: Idiopathic scoliosis accounts for approximately 80% of scoliosis cases and distorts the thoracic cavity during lung development causing a restrictive lung disease. We have recently shown that each 10 o of curve accounts for a fall of approximately 4% in FEV1 /FVC. 1 However, little is known about whether spinal fusion improves lung function in these patients. We performed follow up spirometry on 18 children who had undergone spinal fusion (age 11–16) and compared this to pre-operative values. Aims: To investigate the change in FVC and FEV1 before and after surgery using spirometry, and the relationship between this and the age at surgery and degree of curvature at that time. Methods: Eighteen patients who had previously undergone surgery (aged 11–16) were studied. Current height and arm span (to allow comparison with pre-operative measurements) were measured and spirometry was performed by the lung-function department (who had also undertaken pre-operative measurements). Pre and post-operative data were compared as absolute measures, and as Z-scores, using parametric statistical methods. Results: Contrary to previous reports, there was an increase in lung function in most patients following surgery but this was much more apparent in younger children and in those with a greater Cobb angle. Improvement in FEV1 was statistically correlated with Cobb angle at surgery (Pearson's coefficient=0.513 p=0.027) although changes in FVC did not reach statistical significance (Pearson's=0.42 p=0.07). Younger age at surgery was also significantly predictive of greater improvement for both FEV1 and FVC (Pearson's coefficient=−0.77 and −0.85 respectively p<0.001). Worse lung function pre-operatively predicted greater improvement. Conclusions: Scoliosis surgery does seem to result in improved lung function, particularly FEV1, and this is greater with Cobb angles over 50 o and those with poorer lung function pre-operatively. At smaller angles there is little improvement in lung function. Younger patients may also see greater improvement. Reference: . Saych L, et al . EAPS meeting. Barcelona 2014.